Od umowy o władzę do nietolerancji religijnej. Samuel Rutherford i kontraktualne uzasadnienie prześladowań religijnych - Tulejski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Samuel Rutherford (1600?–1661) was a Scottish Presbyterian minister whose political writings form a part of the controversial literature written during the English Civil War period in the mid-seventeenth century. Most of his political writing was done while he sat as a Scottish commissioner in the Westminster Assembly of Divines. His major political book, Lex, Rex was burned by order of the Restoration Government in 1660, and Rutherford was cited on a charge of treason as its author. In his opinion, in order to form a government men contract with one or more men among themselves, giving to them the authority of rulership. The ruler is under contract to rule according to the higher law for the welfare of all people. Rulership is a trust from the people and is never given without reservation. If the ruler misuses his trust, the people have the right and duty to resist him in order to preserve themselves within the higher law. Knowledge of the higher law comes through reason but reason is fallible. However, God has graciously provided the infallible Scripture as a guide to reason. Rutherford believes there is only one true interpretation of Scripture and that God has given to the Church primary authority in interpretation. In this article, the Author argues that Rutherford’s doctrine of exclusive truth leads him to an uncompromising position of religious intolerance.
Keywords: Rutherford, Samuel; rewolucja purytańska; umowa społeczna; nietolerancja